2018
DOI: 10.7554/elife.36745
|View full text |Cite
|
Sign up to set email alerts
|

Cortical dynein pulling mechanism is regulated by differentially targeted attachment molecule Num1

Abstract: Cortical dynein generates pulling forces via microtubule (MT) end capture-shrinkage and lateral MT sliding mechanisms. In Saccharomyces cerevisiae, the dynein attachment molecule Num1 interacts with endoplasmic reticulum (ER) and mitochondria to facilitate spindle positioning across the mother-bud neck, but direct evidence for how these cortical contacts regulate dynein-dependent pulling forces is lacking. We show that loss of Scs2/Scs22, ER tethering proteins, resulted in defective Num1 distribution and loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 87 publications
9
33
0
Order By: Relevance
“…Similar to Num1 patches in WT cells (Omer et al, 2018), Num1-GFP patches in Mdm36 OX cells redistributed to the polarized ends of the cell (the distal bud tip and the mother cell apex) upon deletion of the ER tethering proteins, Scs2 and Scs22 (Fig. S1C).…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…Similar to Num1 patches in WT cells (Omer et al, 2018), Num1-GFP patches in Mdm36 OX cells redistributed to the polarized ends of the cell (the distal bud tip and the mother cell apex) upon deletion of the ER tethering proteins, Scs2 and Scs22 (Fig. S1C).…”
Section: Resultsmentioning
confidence: 70%
“…In WT cells, cortical dynein pulls the spindle into the bud cell compartment via lateral MT sliding mechanism (Adames and Cooper, 2000). More recently, however, several studies showed that cortical dynein can also pull on the astral MT via end-on MT capture-shrinkage mechanism (Laan et al, 2012; Omer et al, 2018). To assess the mechanism in Mdm36 OX cells, we monitored dynein-dependent astral MT interaction with the bud cortex using a spindle correction assay, scoring for MT behavior during anaphase spindle re-alignment from a misoriented position.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In filamentous fungi and budding yeast, dynein, dynactin and LIS1-NudE all accumulate at the microtubule (MT) plus ends (Han et al, 2001;Efimov, 2003;Lee et al, 2003;Sheeman et al, 2003;Zhang et al, 2003;Li et al, 2005;Lenz et al, 2006;Moore et al, 2008;Callejas-Negrete et al, 2015). The MT plus-end accumulation of dynein is important for spindle-orientation/nuclear migration and for early endosome transport Sheeman et al, 2003;Lenz et al, 2006;Omer et al, 2018;Xiang, 2018). In A. nidulans and Ustilago maydis, the plus-end dynein accumulation depends on dynactin and kinesin-1 but not NudF/LIS1 (Zhang et al, 2003;Lenz et al, 2006;Zhang et al, 2010;Egan et al, 2012;Yao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%